Strategi Penentuan Prioritas Penggalian Potensi Pajak Daerah: Studi Empiris di Provinsi Kepulauan Bangka Belitung - Febrian Yalisman; Dimas Destiana Muhamad Jayadipura; Reza Irfandhani; Annisa Deni Istina; Edih Mulyadi; Devi Valeriani (Jurnal Manajemen Perbendaharaan, 2026)
This study aims to identify strategies for exploring local tax potential following the implementation of Law No. 1 of 2022 in the Bangka Belitung Islands Province. Using a mixed-method approach, this research addresses a gap in the literature that has predominantly been characterized by fragmented approaches in analyzing local tax potential. The quantitative analysis employs panel data regression and ordinary least squares (OLS) on seven regencies/cities over the 2016–2023 period to estimate the decomposition of local tax elasticity with respect to tax bases and sectoral economic activity. Meanwhile, the qualitative analysis applies the Analytical Hierarchy Process (AHP), supported by focus group discussions (FGD) and pairwise comparison questionnaires involving academics, officials from the Ministry of Finance, and local government tax administrators. The results indicate that local tax revenues are inelastic to changes in the tax base, suggesting room for revenue enhancement through improvements in tax administration. Data availability emerges as the most important criterion in determining local tax exploration priorities, while BPHTB, Cigarette Tax, and Motor Vehicle Fuel Tax are identified as the highest-priority taxes for optimization. In addition, differences are found between central and local governments in formulating strategies for local tax optimization. This study contributes to the academic literature by developing a mixed-method approach that integrates empirical estimation of local tax elasticity with expert judgment. Practically, the study provides recommendations for local governments to strengthen tax administration and formulate more targeted tax prioritization strategies in order to support sustainable fiscal independence.